Differential stability of variant OPN1LW gene transcripts in myopic patients - Mountford, Jessica K; Davies, Wayne I L; Griffiths, Lyn R; Yazar, Seyhan; Mackey, David A; Hunt, David M (Molecular vision, 2019)
In Bornholm eye disease, a defect in the splicing of transcripts from a variant opsin gene leads to a depletion in spliced transcript levels and, consequently, a reduction in photopigment in photoreceptors expressing the variant gene. Myopic and age-matched control subjects were drawn from the Western Australian Pregnancy Cohort (Raine) Study and the Norfolk Island Eye Study groups. The opsin gene was amplified using long-range PCR methodology and was fully sequenced. Expression of variant opsins was evaluated using quantitative PCR (qPCR). RNA secondary structure changes arising from identified variants were predicted by modeling. Forty-two nucleotide sites were found to vary across the 111 subjects studied. Of these, 15 had not been previously reported, with three present only in myopic individuals. Expression of these variants in transfected human embryonic kidney (HEK293T) cells demonstrated that splicing efficiencies were not affected. However, gene transcripts from two of the three variants were significantly depleted. RNA secondary structure modeling predicted that these single nucleotide changes could affect RNA stability. None of the variants identified in myopic individuals appeared to alter the efficiency of transcript splicing. However, two resulted in a significant reduction in the number of spliced and unspliced transcripts, indicating an overall reduction in steady-state transcript stability. Such a change would be expected to result in a reduced amount of photopigment, and this may be a contributing factor in the development of myopia.